Analysis of Composite Plates Subjected to Impact Loading (Part II: Numerical Solution) - J. Jweeg, Muhsin; K. Radi, Samera (Journal of Engineering and Sustainable Development, 2007)
The search for a material, which is to be, light and at the same time strong, has resulted in the use of high strength, high modulus fibers reinforced in low strength, low modulus, and low-density matrix material which is called composite material. The finite element models and numerical results are presented for the impact of composite plates using a Special Third Order Theory (HOST 7) with the parabolic distribution of the transverse shear strain through the thickness of the plate and rotary inertia effect is taken into account. The Newmark direct integration method is considered for the solution of the linear dynamic response of the system. A typical finite element mesh of the quarter model is considered because of the double symmetric. A nine-noded Lagrangian element is chosen as a discretization element with seven degrees of freedom per node. The effect of the velocity and mass of the impactor, number of layers, degree of orthotropy (E1/E2), lamination angle, aspect ratio (a/b), and the boundary conditions on the dynamic response of the laminated plate is considered. The results show that the orthotropic ratio, velocity, and mass of the impactor have a significant effect on the deflection of the plate under impact load. In addition, the calculation of the dynamic load factor is presented.